Predicting Chinese older adults' intention to live in nursing homes using an integrated model of the basic psychological needs theory and the theory of planned behavior - Lei, Ming; Deeprasert, Jirawan; Li, Rita Yi Man; Wijitjamree, Natchuda (Frontiers in Public Health, 2022)
The growing number of ageing populations has become a major problem worldwide. Nursing homes play an essential role in the later life of older adults. Previous research indicated potential associations between external factors and older adults’ intention to live in nursing homes. However, intrinsic motivation has yet to be fully understood. This article addresses an academic void that integrated Basic Psychological Needs Theory (BPNT) and the Theory of Planned Behaviour (TPB) to explore older adults’ intentions to live in nursing homes. More specifically, it tested the effects of autonomy, competence, and relatedness needs satisfaction as defined in the BPNT on attitudes, subjective norms, perceived behavioral control, and live in intentions towards nursing homes in the TPB. An online survey provided quantitative data from 425 ageing people. The results indicated that the higher the satisfaction of the basic psychological needs (i.e. autonomy needs, competence needs, and relatedness needs) of the older adults, the lower their intention to live in nursing homes. Furthermore, social pressure partially mediates this relationship. That is, the higher the satisfaction of the basic psychological needs of the older adults, the lower the pressure from society. Thus, they should be admitted to the nursing home, and the lower their intention to live in nursing homes. The results contribute to a better understanding of the deep psychological motivation of the older adults’ intention to live in nursing homes and support further development of the BPNT-TPB model in older adults’ health research.